Regionalizm w historii wychowania w ujęciu Antoniego Karbowiaka (aktualność postulatów i dokonań badawczych) - Wałęga, Agnieszka (Biuletyn Historii Wychowania, 2008)
The article presents the contribution of the first in Poland assistant professor in the field of the history of education, professor of Jagiellonian University, Antoni Karbowiak (1856-1919) to the development of regional historical and educational studies. Karbowiak devoted much attention to the propagation of these studies in his publications, in which he emphasized their import ant role and significance for further development of the history of education. He stressed the need to conduct collective regional studies on a broader scale, according to a precisely defined plan. He contended that only in this way valuable material can be compiled, which - elaborated by well-prepared scholars - shall enable the creation of worthwhile syntheses. He himself undertook “local” research, as he called it, and repeatedly brought readers’ attention to the question of preserving source material found in their closest surroundings for the history of education. He encouraged the creation of regional research organizations and the stimulation of historical consciousness of Polish society, especially children and youth. In order to win new contributors for regional historical and educational studies, he worked out a special 13-point questionnaire on the basis of which it was possible to gather information about local schools and their history. In his publications, Antoni Karbowiak emphasised that even the smallest papers dealing with regional issues are supposed to contribute to the explanation of educational phenomena in broader contexts. This concept by Antoni Karbowiak perfectly combines into the convention of modem regional studies.